2007
DOI: 10.1111/j.1460-9568.2007.05848.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hippocampal function of ovariectomized rats after sequential low doses of estradiol to simulate the preovulatory estrogen surge

Abstract: In adult female rats, robust hippocampal changes occur when estradiol rises on the morning of proestrus. Whether estradiol mediates these changes, however, remains unknown. To address this issue, we used sequential injections of estradiol to simulate two key components of the preovulatory surge: the rapid rise in estradiol on proestrous morning, and the slower rise during the preceding day, diestrus 2. Animals were examined mid-morning of simulated proestrus, and compared to vehicle-treated or intact rats. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 84 publications
(140 reference statements)
10
99
0
Order By: Relevance
“…The significant increase in PSD-95, and nonsignificant increase in pAkt-ir in Val mice during proestrus, is consistent with our previous demonstration that PSD-95-ir and pAkt-ir increase during proestrus in wild-type mice and rats (13,28). Furthermore, the increase in BDNF mRNA during proestrus is consistent with previous studies in female rats, which showed that BDNF mRNA and protein expression increase during proestrus (7,10,11).…”
Section: Estradiol Affects Hippocampal Signaling and Spatial Memory Isupporting
confidence: 92%
See 1 more Smart Citation
“…The significant increase in PSD-95, and nonsignificant increase in pAkt-ir in Val mice during proestrus, is consistent with our previous demonstration that PSD-95-ir and pAkt-ir increase during proestrus in wild-type mice and rats (13,28). Furthermore, the increase in BDNF mRNA during proestrus is consistent with previous studies in female rats, which showed that BDNF mRNA and protein expression increase during proestrus (7,10,11).…”
Section: Estradiol Affects Hippocampal Signaling and Spatial Memory Isupporting
confidence: 92%
“…Increases in circulating estradiol induce hippocampal BDNF mRNA and protein, and increase activation of the BDNF receptor TrkB, in female mice and rats (7)(8)(9)(10)(11)(12)(13). BDNF signaling is important for estradiol to enhance hippocampal synaptic plasticity, because TrkB inhibitors block the estradiol-mediated increase in hippocampal excitability, synaptic protein expression, and dendritic spine formation in rat hippocampal slice cultures (7,14).…”
mentioning
confidence: 99%
“…Increases in CA1 apical spine density are seen after two injections given at this temporal regimen, which corresponded to when our designated behavioral test was given. It should be noted that 10µg injections of 17β-estradiol likely yield greater serum estradiol levels than observed in a cycling female rat (Scharfman et al, 2007;Sims et al, 1996;Woolley and McEwen, 1993), although these levels dramatically decrease within 24 hours of injection (Sims et al, 1996;Woolley and McEwen, 1993). The 5µg dose most likely yields serum estradiol levels within/slightly above the range of that found in a cycling, proestrous rat (Scharfman et al, 2007).…”
Section: Hormone Administrationmentioning
confidence: 99%
“…Thus, it is not entirely clear what is the actual concentration of estradiol acting at receptors in the brain. In addition, although a range of 17b-estradiol doses has been used in different studies, the majority are reported to fall within physiologic levels of plasma estradiol levels; however, higher doses of 17b-estradiol are thought to produce supraphysiological levels of plasma estradiol (MacLusky et al, 2005;Scharfman et al, 2007;Phan et al, 2012;). On the other hand, it has been argued that such concentrations are representative of local estradiol levels within the brain and that such concentrations are required to initiate rapid molecular and cellular responses (see section IV; Cornil et al, 2006;Hojo et al, 2009 for greater discussion).…”
Section: Dose and Routes Of Administrationmentioning
confidence: 99%